Bicarbonate-Stimulated Membrane Reorganization in Stallion Spermatozoa - Maitan, Paula Piccolo; Bromfield, Elizabeth G.; Hoogendijk, Romy; Leung, Miguel Ricardo; Zeev-Ben-Mordehai, Tzviya; van de Lest, Chris H.; Jansen, Jeroen W. A.; Leemans, Bart; Guimarães, José Domingos; Stout, Tom A. E.; Gadella, Bart M.; Henning, Heiko (Frontiers in Cell and Developmental Biology, 2021)
Classical in vitro fertilization (IVF) is still poorly successful in horses. This lack of success is thought to be due primarily to inadequate capacitation of stallion spermatozoa under in vitro conditions. In species in which IVF is successful, bicarbonate, calcium and albumin are considered the key components that enable a gradual reorganization of the sperm plasma membrane that allows the spermatozoa to undergo an acrosome reaction and fertilize the oocyte. The aim of this work was to comprehensively examine contributors to stallion sperm capacitation by investigating bicarbonate-induced membrane remodelling steps, and elucidating the contribution of cAMP signalling to these events. In the presence of capacitating media containing bicarbonate, a significant increase in plasma membrane fluidity was readily detected using merocyanine 540 staining in the majority of viable spermatozoa within 15 min of bicarbonate exposure. Specific inhibition of soluble adenylyl cyclase (sAC) in the presence of bicarbonate by LRE1 significantly reduced the number of viable sperm with high membrane fluidity. This suggests a vital role for sAC-mediated cAMP production in the regulation of membrane fluidity. Cryo-electron tomography of viable cells with high membrane fluidity revealed a range of membrane remodelling intermediates, including destabilized membranes and zones with close apposition of the plasma membrane and the outer acrosomal membrane. However, lipidomic analysis of equivalent viable spermatozoa with high membrane fluidity demonstrated that this phenomenon was neither accompanied by a gross change in the phospholipid composition of stallion sperm membranes nor detectable sterol efflux (p>0.05). After an early increase in membrane fluidity, a significant and cAMP-dependent increase in viable sperm with phosphatidylserine (PS), but not phosphatidylethanolamine (PE) exposure was noted. While the events observed partly resemble findings from the in vitro capacitation of sperm from other mammalian species, the lack of cholesterol removal appears to be an equine-specific phenomenon. This research will assist in the development of a defined medium for the capacitation of stallion sperm and will facilitate progress toward a functional IVF protocol for horse gametes.